Biomimetic nanoparticles for DC vaccination: a versatile approach to boost cancer immunotherapy. Issue 14 (14th March 2023) - Meng, Lingyang; Teng, Zhuang; Yang, Shuang; Wang, Na; Guan, YingHua; Chen, Xiguang; Liu, Ya
Abstract : The incorporation of biomimetic nanoparticles into the DC vaccination strategies has shown outstanding advantages in precisely directing the immune system to fight cancer. Abstract : Cancer immunotherapy, which harnesses the immune system to fight cancer, has begun to make a breakthrough in clinical applications. Dendritic cells (DCs) are the bridge linking innate and adaptive immunity and the trigger of tumor immune response. Considering the cumbersome process and poor efficacy of classic DC vaccines, there has been interest in transferring the field of in vitro -generated DC vaccines to nanovaccines. Conventional nanoparticles have insufficient targeting ability and are easily cleared by the reticuloendothelial system. Biological components have evolved very specific functions, which are difficult to fully reproduce with synthetic materials, making people interested in using the further understanding of biological systems to prepare nanoparticles with new and enhanced functions. Biomimetic nanoparticles are semi-biological or nature-derived delivery systems comprising one or more natural materials, which have a long circulation time in vivo and excellent performance of targeting DCs, and can mimic the antigen-presenting behavior of DCs. In this review, we introduce the classification, design, preparation, and challenges of different biomimetic nanoparticles, and discuss their application in activating DCs in vivo and stimulating T cell antitumor immunity. Incorporating biomimetic nanoparticles into cancer immunotherapy has shown outstanding advantages in precisely coaxing the immune system against cancer.